2022
DOI: 10.18632/aging.204407
|View full text |Cite
|
Sign up to set email alerts
|

The roles of CPSF6 in proliferation, apoptosis and tumorigenicity of lung adenocarcinoma

Abstract: Factor-1 (IGF-1) [9] and Epidermal Growth Factor Receptor (EGFR) [10,11] pathways are frequently disturbed in LUAD. Molecular target therapy has become important parts of LUAD treatment [12,13].Cleavage and polyadenylation specific factor 6 (CPSF6), belonging to the serine/arginine-rich (SR) protein family, is a pre-mRNA splicing factor. CPSF6 was first identified as a component of cleavage factor Im (CFIm) complex [14,15], which plays critical role in mRNA 3' end processing and alternative polyadenylation [16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In contrast, RNA interference transfection with lentiviral vectors is highly efficient ( Esposito and Craigie, 1999 ). We found that HIF-1α was downregulated in the interfering group within 72 h after RNA interference compared with the control group, and it has been reported in the literature that lentivirus interfered with CPSF6 and silenced CPSF6 for more than 7 d ( Zu et al, 2022 ), which suggests that the in vivo expression of lentiviral vectors has a long-lasting inhibitory effect on genes. We observed no adverse effects on PACEs in the UP group, demonstrating that lentivirus is an efficient, durable, and safe transfection vector.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In contrast, RNA interference transfection with lentiviral vectors is highly efficient ( Esposito and Craigie, 1999 ). We found that HIF-1α was downregulated in the interfering group within 72 h after RNA interference compared with the control group, and it has been reported in the literature that lentivirus interfered with CPSF6 and silenced CPSF6 for more than 7 d ( Zu et al, 2022 ), which suggests that the in vivo expression of lentiviral vectors has a long-lasting inhibitory effect on genes. We observed no adverse effects on PACEs in the UP group, demonstrating that lentivirus is an efficient, durable, and safe transfection vector.…”
Section: Discussionsupporting
confidence: 61%
“…In our results, the efficiency of lentiviral transfection of PAECs could reach more than 90%, and the expression of HIF-1α in PACEs was significantly downregulated by RNA interference. It has been reported that the efficiency of transfection of LUAD cells using lentiviral interference with CPSF6 can reach more than 80% ( Zu et al, 2022 ). The methods of transfecting the interfering sequences into cells include chemical synthesis, in vitro transcription and viral vector-mediated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to regulating the antiviral immune responses and orchestrating virus integration, CPSF6 is also involved in cancer progression and immunosuppression. Different studies have reported that the high expression of CPSF6 may be a novel diagnostic and prognostic marker for several tumours, such as hepatocellular carcinoma (HCC) [ 65 ], esophageal squamous cell carcinoma (ESCC) [ 66 ], lung adenocarcinoma (LUAD) [ 67 ] and breast cancer [ 68 ]. We also analyzed The Cancer Genome Atlas (TCGA) data from the TIMER database and found that CPSF6 is significantly high expressed in multiple tumour tissues than in normal tissues ( S8A Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with a high mRNA level of CPSF6 had a worse prognosis and shorter overall or disease-free survival time than those with a low CPSF6 level ( S8B–S8F Fig ). Thus, in addition to its regulatory role in the proliferation, tumorigenicity, and cell death of tumour cells [ 67 69 ], the role of immunosuppression induced by high expression of CPSF6 in tumour progression should also attract more attentions. Interestingly, the expression of miR-377, which often functions as a tumour suppressor [ 70 ], is downregulated in multiple cancer types ( S8G Fig ), further suggesting a significant negative correlation between miR-377 and CPSF6 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation